2005
DOI: 10.1111/j.1365-2850.2005.00846.x
|View full text |Cite
|
Sign up to set email alerts
|

Work stress and physical assault of nursing aides in rural nursing homes with and without dementia special care units

Abstract: Providing more dementia care training and reducing job demands and job strain may help to reduce work-related stress and physical assault of nursing aides employed in nursing homes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
83
1
9

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(98 citation statements)
references
References 24 publications
5
83
1
9
Order By: Relevance
“…A study of nursing aides in rural long-term care settings found that perception of preparedness for dementia care was negatively correlated with job strain (Morgan et al, 2005). The finding that aides in the current study wanted to develop competence in a broader range of activities suggests that job satisfaction of aides could be improved by providing opportunities to use a wider range of skills in caring for clients with dementia.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…A study of nursing aides in rural long-term care settings found that perception of preparedness for dementia care was negatively correlated with job strain (Morgan et al, 2005). The finding that aides in the current study wanted to develop competence in a broader range of activities suggests that job satisfaction of aides could be improved by providing opportunities to use a wider range of skills in caring for clients with dementia.…”
Section: Discussionmentioning
confidence: 58%
“…The increased use of community-based care has implications for the dementia workforce, which plays a central role in the care of people living with dementia (Tsaroucha, Benbow, Kingston, & Mesurier, 2011). Countries that have national plans in place have identified strengthening of the dementia reported a lack of sufficient dementia care skills (Morgan et al, 2002) and dissatisfaction with access to educational programs and resources on dementia (Morgan, Stewart, D'Arcy, Forbes, & Lawson, 2005). The Canadian Home Care Association (2013) identified challenges in education and skills development for both regulated and unregulated home care staff, and it noted that these are exacerbated in rural and remote areas.…”
mentioning
confidence: 99%
“…Although several studies have attempted to quantify the incidence and prevalence of RSA, 26,30,[42][43][44][45][46][47][48][49] their methodologies and results have varied widely, leading to the conclusion that the actual rate of this phenomenon is unknown. 25 Complicating the study of RSA is underreporting both in chart documentation and research studies.…”
Section: Discussionmentioning
confidence: 99%
“…The study identified challenges in providing dementia care in the community 23 and in small rural nursing homes, 24,25 and led to a follow-up study comparing rural facilities with and without dementia special care units. [26][27][28] The early involvement of decision makers has profoundly shaped the research program. A weakness of our early approach, however, was the limited collaboration with decision makers beyond the development of the study questions and design.…”
Section: Launching a Program Of Rural Dementia Care Researchmentioning
confidence: 99%